Two functions f and g , defined on ( − ∞ , ∞ ) and differentiable at least up to order 2, satisfy f ( x + y ) + f ( x − y ) = 2 f ( x ) g ( y ) and g ′ ′ ( 0 ) = 1 .
Find ⌊ ln ( g ( 2 0 1 9 ) ) ⌋ .
Notation: ⌊ ⋅ ⌋ denotes the floor function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First, let's differentiate twice with respect to y . We obtain: f ′ ′ ( x + y ) + f ′ ′ ( x − y ) = 2 f ( x ) g ′ ′ ( y )
By making y = 0 and g ′ ′ ( 0 ) = 1 , we obtain the differential equation f ′ ′ ( x ) + f ′ ′ ( x ) = 2 f ( x ) or f ′ ′ ( x ) − f ( x ) = 0 , with solutions of f ( x ) = C 1 e x + C 2 e − x (1).
Substituting (1) into the original equation gives us: C 1 e x + y + C 2 e − ( x + y ) + C 1 e x − y + C 2 e − ( x − y ) = 2 ( C 1 e x + c 2 e − x ) g ( y )
Using direct calculations, we obtain 2 1 ( e y + e − y ) = g ( y ) or g ( y ) = c o s h ( y ) .
Finally, we evaluate the function at 2 0 1 9 and find ⌊ ln ( g ( 2 0 1 9 ) ) ⌋ .
We obtain that ⌊ ln ( g ( 2 0 1 9 ) ) ⌋ = 2 0 1 8 .
Let us first differentiate the original functional equation twice with respect to y :
f ′ ′ ( x + y ) + f ′ ′ ( x − y ) = 2 f ( x ) g ′ ′ ( y ) ⇒ g ′ ′ ( y ) = 2 f ( x ) f ′ ′ ( x + y ) + f ′ ′ ( x − y ) (i)
and if g ′ ′ ( 0 ) = 1 , then we have:
1 = 2 f ( x ) f ′ ′ ( x ) + f ′ ′ ( x ) ⇒ f ′ ′ ( x ) − f ( x ) = 0 ⇒ f ( x ) = A e x + B e − x (ii)
Substituting (ii) back into the original functional equation now gives:
A e x + y + B e − ( x + y ) + A e x − y + B e − ( x − y ) = 2 ( A e x + B e − x ) ⋅ g ( y ) ;
or A e x ( e y + e − y ) + B e − x ( e y + e − y ) = ( A e x + B e − x ) ⋅ 2 g ( y ) ;
or ( A e x + B − x ) ( e y + e − y ) = ( A e x + B e − x ) ⋅ 2 g ( y ) ;
or e y + e − y = 2 g ( y ) ;
or g ( y ) = 2 e y + e − y = c o s h ( y ) .
Finally, ⌊ l n ( g ( 2 0 1 9 ) ) ⌋ = ⌊ l n ( 2 e 2 0 1 9 + e − 2 0 1 9 ) ⌋ ; ;
or ⌊ l n ( 2 e 2 0 1 9 ( 1 + e − 4 0 3 8 ) ) ⌋ ;
or ⌊ l n ( e 2 0 1 9 ) + l n ( 1 + e − 4 0 3 8 ) − l n ( 2 ) ⌋ ≈ ⌊ 2 0 1 9 − l n ( 2 ) ⌋ = 2 0 1 8 .
Problem Loading...
Note Loading...
Set Loading...
\(\begin{array} {} P(x,y): & f(x+y) + f(x-y) = 2f(x) g(y) & ...(0) \\ P(0,x): & f(x) + f(-x) = 2f(0) g(x) & ...(1) \\ P(0,-x): & f(-x) + f(x) = 2f(0) g(-x) & ...(2) \end{array} \)
From ( 1 ) and ( 2 ) , we note that g ( x ) = g ( − x ) . This means that g ( x ) is even.
\(\begin{array} {} P(x,x): & f(2x) + f(0) = 2f(x) g(x) & ...(3) \\ P(-x,-x): & f(-2x) + f(0) = 2f(-x) \color{blue} g(x) & ...(4) & \small \color{blue} \text{Since }g(x) = g(-x) \end{array} \)
Then ( 3 ) + ( 4 ) :
f ( 2 x ) + f ( − 2 x ) + 2 f ( 0 ) 2 f ( 0 ) g ( 2 x ) + 2 f ( 0 ) g ( 2 x ) + 1 ⟹ g ( 2 x ) = 2 g ( x ) ( f ( x ) + f ( − x ) ) = 2 g ( x ) ⋅ 2 f ( 0 ) g ( x ) = 2 ( g ( x ) ) 2 = 2 ( g ( x ) ) 2 − 1 . . . ( 5 ) ( 1 ) : f ( x ) + f ( − x ) = 2 f ( 0 ) g ( x )
It would appear that g ( x ) = cos x , so that cos ( 2 x ) = 2 cos 2 x − 1 . But g ′ ′ ( x ) = − cos x and g ′ ′ ( 0 ) = − 1 = 1 . Therefore g ( x ) = cos x .
Instead, it is g ( x ) = cosh x = 2 e x + e − x . Then 2 ( g ( x ) ) 2 − 1 = 2 ( 2 e x + e − x ) 2 − 1 = 2 e 2 x + e − 2 x = g ( 2 x ) ; and g ′ ′ ( x ) = cosh x , ⟹ g ′ ′ ( 0 ) = 1 . And f ( x ) = e x . Then P ( x , y ) = f ( x + y ) + f ( x − y ) = e x + y + e x − y = 2 e x ( 2 e y + e − y ) = 2 f ( x ) g ( y ) , proving f ( x ) = e x and g ( x ) = cosh x satisfy the functional equation.
Therefore, ⌊ ln ( g ( 2 0 1 9 ) ) ⌋ = ⌊ ln ( cosh 2 0 1 9 ) ⌋ = 2 0 1 8 .